Auditory neuropathies and electrocochleography. (September 2013) - Santarelli, Rosamaria; del Castillo, Ignacio; Starr, Arnold
Abstract: Auditory neuropathy (AN) is a hearing disorder characterized by disruption of temporal coding of acoustic signals in auditory nerve fibres resulting in impairment of auditory perceptions relying on temporal cues (1, 2 ). Mechanisms suggested include both pre-synaptic and post-synaptic disorders affecting inner hair cell (IHC) depolarization, neurotransmitter release from ribbon synapses, spike initiation in auditory nerve terminals, loss of nerve fibres and impaired conduction, all occurring in the presence of normal physiological measures of outer hair cell (OHC) activities (otoacoustic emissions (OAEs) and cochlear microphonic (CM)). Disordered synchrony of auditory nerve discharge has been suggested as the basis of both the profound alterations of auditory brainstem responses (ABRs) and impairment of speech perception (3 ). We review how electrocochleography (ECochG) can provide detailed information to help define objectively the sites of auditory neural dysfunction as affecting IHC receptor summating potential (SP) and compound action potential (CAP), the latter reflecting disorders of ribbon synapsis and auditory nerve fibres.